ANALISIS SIKAP MAHASISWA MEMILIH MASUK PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNTAN ANGKATAN TAHUN 2022 - Wijayanti, Poppy; Witarsa, Witarsa; Kuswanti, Heni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research was performed on the Faculty of Teacher Training and Education, Tanjungpura University, Pontianak. This research aims to find out: 1) Attitudes of Students Choosing to Enter the Economics Education Study Program FKIP Untan Class of 2022 in Cognitive Aspects, 2) Attitudes of Students Choosing to Enter the Economics Education Study Program FKIP Untan Class of 2022 in Affective Aspects, 3) Attitudes of Students Choosing to Enter Untan FKIP Economic Education Study Program Class of 2022 in Conative Aspects. The research approach used in this study is a qualitative approach with a phenomenological type. Data collection used interview and documentation techniques with 8 informants. The results of the study found that the attitudes of 2022 FKIP Untan Economics Education students in the cognitive aspects included: (1) Knowledge, (2) Perspective, (3) Belief. Of these three things, the attitude of students in the cognitive aspect is positive even though for various main reasons in choosing to enter the FKIP Untan economics education study program. The attitude of students of Economics Education FKIP Untan class of 2022 in the affective aspect includes feelings of likes and dislikes, students of economics education FKIP Untan class of 2022 have a feeling of liking choosing to enter this study program supported by their interests, emotional experiences, social perceptions, interpersonal relationships and factors environment. The attitude of students of Economics Education FKIP Untan class of 2022 in the conative aspect has positive behavior even though there are obstacles when carrying out lectures.